Analysis of the military hospital, Port Louis, Mauritius - Makins, Tessa (School of Architecture, Planning and Geomatics, 2023)
Through a case study of the Military Hospital Complex in Port Louis, Mauritius, the influence of the World Heritage Program of the United Nations Educational Scientific and Cultural Organisiation (UNESCO), in Mauritius is analysed. The new Intercontinental Slavery Museum, a destination on the UNESCO Slave Route, is housed in the Military Hospital Complex. The museum's stated intention is to narrate the shared history of all Mauritians, regardless of their provenance. It aims to explain the role played by the island as a pivotal connection point in the Indian Ocean slave trade from the 18th Century. The Military Hospital Complex is the oldest surviving building on the island (completed 1740). It was built by the French colonists, Mauritius' first permanent inhabitants. The building has a multi-layered history as it has been integral to life on the island, through changing administrations for more than 280 years. The role of the building has adapted over its life span, reflecting the changing political and social dynamics of the country. Responding to the forces of globalisation in the 1990s the Government of Mauritius engaged with the UNESCO World Heritage Program. The focus of this analysis is on how this Government engagement with UNESCO has affected the creation of modern heritage resources within the country through this case study of the Military Hospital Complex as the Intercontinental Slavery Museum. Methods employed have been to obtain a biographical understanding of the building through archival research, site visits and relevant literature. The historical, political, social, and legislative context of the building over its life, and relating to its transformation into a modern heritage resource have been investigated through relevant literature. Theoretical frameworks of heritage construction in multi-cultural societies have been employed in guiding this research. The UNESCO World Heritage Conventions are discussed, in addition to the various UNESCO treaties, declarations and programs that cumulatively influenced the realisation of Mauritius' World Heritage Sites. The social processes within the country that led to the Truth and Justice Commission in 2010 are investigated. One of the principal recommendations of the Truth and Justice Commission of Mauritius was the creation of a new Intercontinental Slavery Museum in Port Louis. The political ramifications of Mauritius' two World Heritage Sites within the local and global contexts are discussed. The Mauritian political construct that defines the population into groups based on the places of origin of their forebears is at the heart of the way modern heritage has been constructed in the country in association with UNESCO to date. Heritage remains contested and highly politicised in the country. This study has been limited by the politically sensitive nature of heritage within the country and interviews were difficult to secure. The difficulties encountered in conducting research for this analysis has affirmed that these sensitivities prevail. Almost without exception, government officials, heritage professionals and academics were reluctant to discuss the heritage program of the country on or off the record. The researcher was denied access to the case study building. This research concludes that although the vison of Mauritius' new Intercontinental Slavery Museum (housed in the Military Hospital Complex), is comprehensive and inclusive, the political construct of the country remains an impediment to the narration of Mauritian heritage. The heritages of the different groups of people who collectively comprise the Mauritian population have, to date, been separately told. The new museum has a role to pay in narrating the role played by Mauritius within the Indian Ocean slave trade, a story that has relevance to all Mauritians regardless of their population group.